Preliminary evaluation of early wheat lines (Triticum aestivum L.) (Semiárida, 2020)
With the aim to determine the yield's level reached in theWheat Genetic Improvement Programe were evaluated twenty homozygote’s line (F6). The check varieties were: Bordenave Puán SAG, Buck Pucará y Buck Pangaré. Was utilized the statistical methodology developed by W. T. Federer. These designs have the advantage over other statistical designs its utilization in early screening trials when the seed's availability is a trouble. Sixty percent of the tested lines yields than the best check variety.